Reflexive Ethnographic Practice
XXIV, 219 p. 28 illus., 26 illus. in color.
Keywords: “This moving book offers a profound vision of all that reflexive ethnography can be if carried out with sensitivity, humility, and respect for the multiple layers of history in which our work is always enmeshed.” —Ruth Behar, Professor at the University of Michigan, USA, and author of Traveling Heavy: A Memoir in Between Journeys “In essays which span forty years of immersion in Yanyuwa culture and ethnographic fieldwork, the authors reflect on their professional practices through the lens of self-scrutiny, discomfort, uncertainty and awe, exploring the tensions and contradictions between academic rigour and the visceral apprehension of different ways of perceiving the world. This book is a timely and essential contribution to the increasingly complex discourse around how to live with, work with, and write about Indigenous people.” —Kim Mahood, award-winning Australian author and artist Putting the anthropological imagination underthe spotlight, this book represents the experience of three generations of researchers, each of whom have long collaborated with the same Indigenous community over the course of their careers. In the context of a remote Indigenous Australian community in northern Australia, these researchers—anthropologists, an archeologist, a literary scholar, and an artist—encounter reflexivity and ethnographic practice through deeply personal and professionally revealing accounts of anthropological consciousness, relational encounters, and knowledge sharing. In six discrete chapters, the authors reveal the complexities that run through these relationships, considering how any one of us builds knowledge, shares knowledge, how we encounter different and new knowledge, and how well we are positioned to understand the lived experiences of others, whilst making ourselves fully available to personal change. At its core, this anthology is a meditation on learning and friendship across cultures.